Síntese e estrutura de compostos poliaza heterocíclicos - Campos, Patrick Teixeira (2012)
This work describes the synthesis of a number of polyaza heterocycles and the mechanistic study to obtain these products. Furthermore, the characterization was performed by spectroscopic method and the structural study by X-ray diffraction and theoretical calculations of molecular orbitals. The synthesis of polyaza heterocyclic compounds began from the cyclocondensation reaction between a β- enaminodiketone and 2-aminopyridine, 2-aminothiazole or 2-aminobenzoimidazole in order to achieve pyrido[1,2-a]pyrimidin-4-one, thiazole[3,2-a]pyrimidin-5-one or 2- oxo-pyrimido[1,2-a]benzimidazole, respectively, with a α-keto ester substituent, in high regioselectivity. The mechanistic proposal developed in this step is based on the semi-empirical theoretical calculations by the PM3 method. From these data it was possible to say that the reaction was controlled by frontier molecular orbital, according to values of HOMO/LUMO coefficient obtained for the reactants. In the next step, the α-keto esters previously obtained, were reacted with ethylenediamine and derivatives ledding to the pyrazinones formation and the reaction with 1,2- phenylenediamine and derivatives led to the formation quinoxalinones. The same reaction of α-keto esters with amidines did not lead to the formation of imidazolonas as expected, since only the formation of the substitution product in the ester group occurred. The reaction mechanisms proposed in these steps are also based in theoretical calculations, where it was possible to infer that the reaction was thermodynamically controlled, since the reactivity sites were less important than the stability of the intermediates. The compounds were characterized by 1D nuclear magnetic resonance experiments of such as 1H and 13C and 2D such as COSY, HETCOR and HMBC, besides of mass spectrometry. The molecular structural studies by X-ray diffraction (for the compounds that could be measured) revealed that polyaza heterocycles pyrido[1,2-a]pyrimidin-4-one, thiazole[3,2-a]pyrimidin-5-one and 2-oxo-pyrimido[1,2-a]benzimidazole are essentially plane. All these compounds showed as pattern at least one intramolecular interaction between a carbonyl oxygen atom and a carbonyl carbon via π-hole, forming a five membered pseudo-ring, which stabilizes the position of a carbonyl group. The study revealed that all structural supramolecular compounds exhibit a large number of weak hydrogen bonds of the type CH···X (where X = O, N) and the compounds which exhibited a NH group in its structure or water in the asymmetric unit formed additionally strong hydrogen bonds of the type X-H···X (where X = O, N). Since the structures studied are aromatic heterocycles, all compounds showed interactions involving π systems in their interactions like π···π and/or lone-pair···π in their crystal packing. Only one intermolecular interaction via σ-hole (C=O···S) and another via π-hole (C=O···C=O) were found.